Expression of p53, cyclin D1 and EGFR correlates with histological grade of adult soft tissue sarcomas: a study on tissue microarrays - Veselý, Karel; Jurajda, Michal; Nenutil, Rudolf; Veselá, Marcela (Neoplasma, 2009)
Soft tissue sarcomas (STSs) are rare heterogeneous tumors with variable clinical course and outcome. The management of STSs depends upon the accurate histopathological diagnosis and assessing their histological grade. Currently, core needle biopsies are becoming increasingly popular for diagnosing STSs but value of histological grading is limited from this type of specimens. To evaluate the immunohistochemical expression of p53, mdm-2, cyclin D1, p16, nm23, EGFR and Ki-67 labelling index in adult STSs patients and their association with histological grade of STSs, we analysed 101 primary untreated STSs of the limbs and trunk using the tissue microarray technique on formalin-fixed, paraffin-embedded tissue samples. The cases consisted of 15 G1, 28 G2 and 58 G2 sarcomas. Ki-67 labelling index (LI) was calculated from whole block sections for the possibility to select the most proliferative regions. The LI ranged from 1.26 to 75.5% (median 26.7%) and strongly correlated with the mitotic count (p rs for adult patients with STSs and may assist in establishment of the histological grade in STSs.
Keywords: Tissue Array Analysis; dospělí; Tumor Suppressor Protein p53; NM23-nukleosiddifosfátkinasy; Sarcoma; Female; ErbB Receptors; erbB receptory; cyklin D1; Adult; ženské pohlaví; Adolescent; Immunohistochemistry; lidé; Aged, 80 and over; čipová analýza tkání; imunohistochemie; Cyclin D1; sarkom; Male; Aged; nádorový supresorový protein p53; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; NM23 Nucleoside Diphosphate Kinases; Middle Aged; mladiství; Humans